Analysis of the Contribution of Capital Structure, Accounting Information Systems, Financial Management and Spirituality to MSME Business Sustainability in Central Lombok Regency - Ningsih, Pipin Sulistia; Jumaidi, Lalu Takdir (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study seeks to examine the influence of capital structure, accounting information systems, financial management, and spirituality on the sustainability of MSMEs in Central Lombok Regency. A quantitative method with an explanatory approach is employed in this research. A sample of 30 MSMEs was selected purposively, namely business actors who have used accounting information systems and have financial reports. Data analysis was performed using the SEM-PLS technique and SmartPLS 4 software. The findings demonstrate thatcapital structure significantly improves SMEs' sustainability. In contrast, accounting information systems, financial management, and spirituality did not show a significant effect. These results indicate the importance of optimally managing capital structure to support business sustainability. This research indicates the need to strengthen financial literacy and digitalization of accounting information in MSMEs.